Correlation of HBsAg quantitation by ELISA with serum hepatitis B virus DNA quantitative PCR in chronic hepatitis B patients - Kolassery, Sandesh (International Journal of Research in Medical Sciences, 2017)
Background: Serum HBV DNA is a useful and reliable marker to diagnose and monitor CHB on treatment. The limitation of HBV DNA is that it is expensive and that the assays lack uniformity and standardization. Hence there is a need for more economical and reliable marker. HBsAg quantitation is one such surrogate serological marker. The objective of the current study is to compare and correlate the serum hepatitis B DNA quantitative PCR with HBsAg quantitation. Methods: Patients with CHB attending to the outpatient clinic of Gastroenterology department were enrolled in the study. Patients with undetectable HBV DNA levels and those co-infected with HCV or HIV were excluded from the study. All patients were tested for serological markers like HBsAg (rapid), HBeAg, anti HBe and HBV DNA-PCR. HBsAg quantification was done using conventional ELISA immunoassay. HBV-DNA and qHBsAg levels were expressed in log10IU/ml. Pearson correlation was used to estimate correlation between HBV DNA and HBsAg quantitation. Statistical analysis was done using SPSS and P value of <0.05 was considered significant. Results: A total of 38 patients were enrolled in the study. 23.62% were females and mean age of patients in the entire study group was 35.72 years. The mean ALT level was 103.80U/L. 26.32% (n = 10) were HBeAg positive. Mean HBV DNA and qHBsAg levels for the entire cohort were 5.81 log10IU/ml and 5.83 log10IU/ml respectively with a correlation coefficient of 0.318 (P = 0.130). For HBeAg positive patients the mean HBV DNA and qHBsAg levels were 7.90 log10IU/ml and 5.91 log10IU/ml respectively with a correlation coefficient of 0.722 (P = 0.043). HBV DNA levels were significantly higher in HBeAg positive patients compared with HBeAg negative patients (7.9 versus 4.01; P = 0.002). qHBsAg levels were also marginally high in HBeAg positive patients (5.91 versus 5.8; P = 0.136). Neither HBV DNA levels nor qHBsAg levels correlated with serum ALT levels. Conclusions: There is a significant correlation between quantitative HBsAg levels and HBV-DNA levels in HBeAg positive patients with chronic hepatitis B but not in HBeAg negative patients. HBV-DNA levels are significantly higher in HBeAg positive patients.